(untitled) (Malaysian Journal of Civil Engineering, 2018)
Density currents occur when fluid of one density propagates along a horizontal boundary into fluid of a different density. They are also called turbidity currents when the main driving mechanism is from suspended sediments. Reservoir sedimentation is often related to sediment transport by turbidity currents. The leading edge of a density current is deeper than the following current and is called head or front. In this paper, the effects of bed roughness on density currents propagation were studied. Experiments were carried out over a smooth bed as well as three artificially roughened beds by cylindrical roughness elements. Temporal and spatial evolutions of the current front were analyzed. In experiments performed over rough beds, the measured head velocities were smaller than that of smooth bed. The observed trend is that as the surface roughness increases the front velocity decreases